Hypoglycemic and Antioxidative Effects of Pomegranate (Punica granatum L.) Juice in Streptozotocin Induced Diabetic Rats - Prasetyastuti; Anthony, Mochammad Willy Pratama; Rahman, Nuha Aulia; Ngadikun; Sunarti (Pakistan Journal of Nutrition, 2014)
Diabetes mellitus is a metabolic disorder that is characterized by hyperglycemia and associated with increased oxidative stress. The polyphenol property in pomegranate juice was reported to have significant antioxidant effect. The present study aims to investigate the hypoglycemic and antioxidative effect of pomegranate juice in streptozotocin-induced diabetic rats. Twenty healthy male rattus norvegicus with age of eight weeks and weighing at average of 200 g were randomly assigned into four groups. Diabetic models were induced by using 60 mg/kg body weight (BW) streptozotocin (STZ) intraperitoneally. The rats were allocated into four groups, group treated with 0.1 mg/kg BW glibenclamide, groups supplemented with 1, 2 and 4 mL/200 g BW pomegranate juice, respectively. Evaluation of hypoglycemic and antioxidative effect were performed by measuring blood glucose level, lipid peroxidation, including malondialdehyde (MDA) and advanced glycation end-product (AGE) before and after treatment. Lipid profile was also measured before and after treatment. Treatment with glibenclamide and supplementation with three different doses of pomegranate juice in diabetic rats were significantly reduced blood glucose level. Supplementation with 2 mL/200 g BW pomegranate juice was significantly reduced MDA concentration, whereas the AGE concentration was not significantly decreased by pomegranate juice supplementation. Lipid profile related to total cholesterol and triglyceride levels were not significantly reduced. Furthermore, high density lipoprotein was not increased significantly after each treatment. Pomegranate juice has hypoglycemic and antioxidative effects in streptozotocin-induced diabetic rats.